Evaluation of comfort preferences and insights into behavioural adaptation of students in naturally ventilated classrooms in a tropical country, India. (1st October 2018) - Kumar, Sanjay; Singh, Manoj Kumar; Mathur, Anuj; Mathur, Jyotirmay; Mathur, Sanjay
Abstract: A transverse questionnaire based thermal comfort field study was conducted in 30 naturally ventilated university classrooms during peak summer months in composite climate of India. A detailed statistical analysis was carried out on 900 thermal comfort surveys database containing information about sensation and preference for different indoor environmental variables. Neutral temperature predicted through linear regression method varied more than 3 °C for different surveyed buildings. More than 90% comfortable votes (±1 votes) of the present database do fit within adaptive comfort boundaries for this climatic zone of India. Additionally, the study estimated a preferred temperature of 26.4 °C using probit analysis. During the field study, personal and global adaptive actions (adaptive actions that tend to modify the indoor environment of classroom) of students during regular classes were recorded and analyzed. Analysis concluded that students preferred high air speed ranges for restoring comfort either by opening windows and doors as or by operating ceiling fans. Logistic regression model predicts more than 80% ceiling fan usage at indoor air temperature 29 °C. Highlights: This study provides insights and interrelations among different adaptive actions in a classroom. Probit analysis shows preferred temperature of 26.4 °C. Controlling air speed by operating ceiling fans, opening of windows and doors are primary adaptive action. Logistic regression model predicts more than 80% fan uses at 29 °C in naturally ventilated classrooms.